IMPLEMENTASI PENGEMBANGAN KELEMBAGAAN PADA PROGRAM PENGELOLAAN HUTAN BERSAMA MASYARAKAT (PHBM) DI KESATUAN PEMANGKUAN HUTAN (KPH) BLORA - Hendri Insani Prabowo; Margaretha Suryaningsih (Journal of Public Policy and Management Review, 2018)
In 2009 Perhutani issued Decree of the Perum Perhutani Board of Directors Number: 682 / Kpts / Dir / 2009 About the Guidelines of Community Forest Resources Management as the latest regulation since the establishment of PHBM Program since 2001. But the implementation of regulatian in Blora Forest Management Unit (KPH) its not significant and equitable impacts such as what is the purpose of CBFM itself, which improves the ecological, social and economic functions of forest village communities. So researchers interested in doing this research. The implementers of this program are KPH Blora, Local Government, Forest Village Community Institution (LMDH), Village Government and NGO. This research uses Marilee S. Grindle theory. Successful implementation according to Merile S. Grindle is influenced by two big variables, namely the content of policy and the context of implementation. This research uses qualitative method with data collection technique that is interview, direct observation and documentation. The results of this study indicate that the implementation of Institutional Development in Community Forest Management Program (PHBM) in the Forest Management Unit Unit (KPH) Blora not running maximally